Characterization of solid waste in the Los Roques Archipelago National Park, Venezuela: - Hernández, Vanessa (2025)
Introduction: Solid waste can have significant environmental and public health impacts, especially in protected areas such as the Los Roques Archipelago National Park (LRANP), where tourism is intense. Objective: To characterize the solid waste generated by households, hostels, and businesses in LRANP. Methodology: A stratified random sampling was carried out during one week in November 2022. Waste was classified by type, volume, and loose density, following the method proposed by Cabañas-Pinedo, Díaz-Sánchez & Oliva (2019). Results: A total of 823.25 kg of solid waste was recorded, with organic matter as the dominant category (58%), followed by plastic, paper/cardboard, and glass. Hostels were the largest contributors (19.76 kg/day), followed by households (13.18 kg/day) and businesses (5.44 kg/day). Plastic had the highest volume, while glass had the highest loose density (0.93 kg/m³). Waste generation increased on days with higher tourist activity (Thursday to Saturday). Conclusions: Waste generation is strongly influenced by tourism. The results underscore the need for an integrated waste management strategy tailored to island conditions, with emphasis on prevention, recycling, and community education.